Horizontal Bone Augmentation in the Anterior Esthetic Area of the Maxilla Using a Flap Design Adapted from Mucogingival Surgery in Association with PLA Membrane and β-TCP - Canullo, Luigi; Tronchi, Mauro; Kawakami, Shunsuke; Iida, Takahisa; Signorini, Luca; Mordini, Lorenzo (The International journal of periodontics & restorative dentistry, 2019)
Systematic reviews showed possible esthetic complications with the use of traditional flap designs after guided bone regeneration (GBR) procedures in the esthetic zone and the aim of this case series was to analyze hard and soft tissue changes over 18 months after these procedures. Healthy subjects requiring tooth extraction and single-implant placement in the anterior maxilla were enrolled in the study. Three months after tooth extraction and ridge preservation, a prosthetic-driven implant was placed. The horizontal bone deficiency was treated with a resorbable bone graft substitute (beta tricalcium phosphate [β-TCP]) and a bioresorbable polylactic acid (PLA) membrane. Primary closure was obtained by a novel coronally advanced flap adapted from mucogingival techniques. Final metal-free implant restorations were delivered 4 months after placement. Clinical measurements, pictures, and radiographs were acquired after delivery of the final restoration (T1) and at the 18-month follow-up (T2). Digital impressions were taken at the time of tooth extraction (T-1) and implant insertion (baseline; T0) and at T2. Marginal bone level changes were assessed by radiographic analysis, while soft tissue changes were evaluated with ExoCad software. Student t test for paired data was used to detect differences between the different time points. Twelve subjects (7 men and 5 women; mean age: 63.7 ± 14 years) completed the study and received 15 implants. All implants healed uneventfully and were clinically osseointegrated and stable, showing no sign of infection. No GBR complications were noted. Statistically significant ridge-width changes were observed after extraction (T-1 vs T0 = -1.72 ± 0.30 mm; P = .00001) and after horizontal GBR (T0 vs T2 = 1.41 ± 0.64 mm; P = .00001). Radiographic bone levels after implant placement remained stable T0 to T2 (0.09 ± 0.08 mm). Periodontal parameters never exceeded physiologic levels. It can be concluded that GBR using a bioresorbable PLA membrane and resorbable β-TCP bone graft in conjunction with a coronally advanced flap is a predictable procedure for horizontal bone augmentation with simultaneous implant placement in the esthetic area.